The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ldr.3542
|View full text |Cite
|
Sign up to set email alerts
|

Vertical changes in bacterial community composition down to a depth of 20 m on the degraded Loess Plateau in China

Abstract: Soil microbes are involved in the fundamental processes that underpin an ecosystem's function. However, little is known about the microbial communities that inhabit deep soil horizons, especially in degraded forest ecosystems. Here, we used high‐throughput sequencing to investigate the vertical distribution of soil bacterial communities to a depth of 20 m in Pinus tabulaeformis and Robinia pseudoacacia forests on the Loess Plateau, China. We found that bacterial richness declined from the topsoil to a depth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
3
14
0
Order By: Relevance
“…We found high actinobacterial abundances in both, loess and paleosols, although Actinobacteria appeared to be especially predominant in weakly developed soil horizons. This is consistent with recent studies which report that Actinobacteria were abundant in semi-arid loess soils 32,53 and more abundant under alkaline soil conditions 53 , as in our study. Actinobacteria with high relative abundances were e.g.…”
Section: Do Taxa Which Are Presumed Members Of Old Mcs Provide Informsupporting
confidence: 94%
See 2 more Smart Citations
“…We found high actinobacterial abundances in both, loess and paleosols, although Actinobacteria appeared to be especially predominant in weakly developed soil horizons. This is consistent with recent studies which report that Actinobacteria were abundant in semi-arid loess soils 32,53 and more abundant under alkaline soil conditions 53 , as in our study. Actinobacteria with high relative abundances were e.g.…”
Section: Do Taxa Which Are Presumed Members Of Old Mcs Provide Informsupporting
confidence: 94%
“…3). This overall decline in alpha diversity and abundance is well known from studies of other soil profiles, which analyzed www.nature.com/scientificreports/ profiles up to 20 m deep [29][30][31][32] . It is primarily reflecting the decreasing microbial population size with increasing depth.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Some groups of microorganisms appear predominantly in deeper soil horizons, such as the candidate phylum Dormibacteraeota (Brewer et al, 2019), or tree root host-specific mycorrhizal fungal strains, as shown in Eucalyptus forests at 4 m soil depth (Robin et al, 2019). Also, it appears that microbial diversity is not necessarily lower in subsoils than in topsoils, as recently has been found on the Loess Plateau in China in soils down to 20 m depth (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 71%
“…In general, living conditions for soil organisms and roots are harsher in deeper soil layers, where the soil density is higher, oxygen concentrations are lower, and carbon and nutrients are less available (Lennon, 2020). Carbon and nutrients typically are more available in the upper soil, mainly due to larger quantities of leaf and fine root litter and root exudates, as well as more biotic activity (Eldridge et al, 2016;Liu et al, 2020). Consequently, microbial biomass is usually one to two orders of magnitude lower in the subsoil than in the topsoil (Eilers et al, 2012;Spohn et al, 2016).…”
Section: Introductionmentioning
confidence: 99%